A rare variation of the biceps brachi muscle - Paval J; Mathew J (Indian Journal of Plastic Surgery)
Biceps brachii muscle is very variable. Biceps may be composed of one to five heads. Although the variations in the origin are plenty, there are a very few cases reported on the variations in the insertion of the biceps brachii muscle. In this report we present a variant biceps brachii muscle which gives an abnormal muscle fasciculus from its medial side which continues as a narrow tendinous slip and is inserted in to the medial supracondylar ridge of humerus. We discuss in this report, the possible median nerve entrapment due to the presence of such a variation.